COVID-19 in Nigeria : Frontline Data and Pathways for Policy - Lain, Jonathan William (World Bank, Washington, DC, 2021)
The COVID-19 (coronavirus) pandemic and its economic and social effects on households have created an urgent need for timely data to help monitor and mitigate the social and economic impacts of the crisis and protect the welfare of Nigerian society. To monitor how the COVID-19 pandemic is affecting the economy and people of Nigeria and to inform policy interventions and responses, the National Bureau of Statistics with technical support from the World Bank implemented the Nigeria COVID-19 National Longitudinal Phone Survey (NLPS) from April 2020 to April 2021. This report draws on NLPS and other relevant data to analyze COVID-19 impacts in Nigeria’s human capital, livelihoods and welfare. It also looks ahead to the broad challenges of building back better in Nigeria and summarizes priorities for policymaking and implementation.